Reflections of Contemporary Islamic Law to The Spirit Doll Phenomenon; A Sadd Al-Żarī'ah Perspective - Bakry, Muammar; Ilham, M.; Musyahid, Achmad; Mundzir, Chaerul; Ramli, Arif Rahman (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
People are restless in the wake of the growing popularity of spirit dolls in recent years. Contemporary Islamic legal clarity is required when determining whether the spirit doll phenomenon is true or false. The purpose of this article is to respond to a study of contemporary Islamic law concerning the spirit doll phenomenon that has alarmed the public. This is a qualitative study that takes a socio-normative approach. Sadd al-żarī'ah is used as a method for tracking (istinbat) Islamic law. The study's findings revealed that people caring for spirit dolls were motivated by a lack of faith and knowledge, dynamism and animism, as well as hedonism. According to Islamic law's teachings, the spirit doll phenomenon is forbidden and must be abandoned. Ulama gathered in South Sulawesi Province's Indonesian Ulema Council (MUI) and agreed to prohibit this phenomenon. The implication is that the spirit doll is manifested in every person whose physical body has a shadow or is physically shaped like a human or animal statue. It is, however, prohibited or permitted for girls' toys only. It is hoped that Muslims will avoid practices that could jeopardize religious values by abstaining from the use of spirit puppets.